Older Adults' Recognition of Trade‐Offs in Healthcare Decision‐Making. Issue 8 (14th July 2015) - Case, Siobhan M.; O'Leary, John; Kim, Nancy; Tinetti, Mary E.; Fried, Terri R.
<x xml:space="preserve">Abstract</x> Objectives To examine older persons' understanding of healthcare decision‐making involving trade‐offs. Design Cross‐sectional survey. Setting Primary care clinics. Participants Community‐living persons aged 65 and older (N = 50). Measurements After being primed to think about trade‐offs with a focus on chronic disease management, participants were asked to describe a decision they had made in the past involving a trade‐off. If they could not, they were asked to describe a decision they might face in the future and were then given an example of a decision. They were also asked about communication with their primary care provider about their priorities when faced with a trade‐off. Results Forty‐four participants (88%) were able to describe a healthcare decision involving a trade‐off; 25 provided a decision in the past, 17 provided a decision they might face in the future, and two provided a future decision after hearing an example. One participant described a nonmedical decision, and two participants described goals without providing a trade‐off. Of the healthcare decisions, 26 involved surgery, seven were end‐of life decisions, seven involved treatment of chronic disease, and four involved chemotherapy. When asked whether their providers should know their health outcome priorities, 44 (88%) replied yes, and 35 (70%) believed their providers knew their priorities, but only 18 (36%) said that they had had a specific conversation about priorities. Conclusion The majority of participants were able to recognize the trade‐offs involved in healthcare decision‐making and wanted their providers to know their priorities regarding the trade‐offs. Despite being primed to think about the trade‐offs involved in day‐to‐day treatment of chronic disease, participants most frequently described episodic, high‐stakes decisions including surgery and end‐of‐life care.